TEACHING TRANSACTIONAL AND INTERPERSONAL CONVERSATION: A CLASSROOM ACTION RESEARCH - Priyatmojo, Arif Suryo (Language Circle: Journal of Language and Literature, 2014)
Based on the standard competence of Indonesianâs curriculum relating to speaking activities, the students are demanded to express meaning/ messages in both transactional and interpersonal conversation using spoken languages in every context of situation. Two different kinds of conversation have their own characteristics, from which we still encounter students facing difficulties to communicate with others. The study was aimed at describing whether by giving different time allocation for the students to practice doing transactional and interpersonal conversation can impove the studentsâ conversation skills. It is a classroom action research conducted in my own class; the students in a transactional and interpersonal class became the subject of the study. The class consisted of 24 students in the second semester in the academic year of 2012-2013. To collect the data, I used four ways of collecting data in the forms of observation, questionnaire, interview and video recording. Those four different ways of collecting data were used at initial, middle and final teaching learning process to measure the progress of the study. Time allocation was my teaching technique to improve the students conversation skill. Based on the result of the study, I found that time allocation has positive significance for the studentsâ conversation activities. This improvement was validated by involving a critical colleague and research participants. It can be seen that the students could conduct conversations in longer period of times for both transactional and interpersonal conversations using different degrees of formality, topic preferences, language uses, mode, purposes and cultural contexts. This suggests that the students need longer time to practice by which they are able to do conversation with others in very meaningful ways.